Retail Service Quality and Customer Loyalty - Kartika Sekar Ayuningtias; Trisha Gilang Saraswati (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
IKEA Alam Sutera is a conventional furniture company with the theme of self-service shopping that is still new to the people of Indonesia. There is a retail service quality that is a variable on the experience of consumers in receiving IKEA services that have problems in them and cause dissatisfaction from customers, therefore the customer satisfaction variable is used in this study. It also has the aim to know whether customers can still be loyal to IKEA with the customer loyatly variable. The sample of this research was 100 respondents who were IKEA consumers who had made purchases at least 2 times. Location of this research at IKEA Alam Sutera offline store at Tanggerang Indonesia and the respondents answer the question by google form. The data analysis technique used is descriptive analysis and path analysis with the help of SPSS version 23 software. The results of this research were first there is a direct influence of retail service quality on customer satisfaction of 21.5%. Second, there is a direct influence of retail service quality on customer loyalty of 21%. Third, there is a direct effect of customer satisfaction on customer loyalty of 18.7%. Finally, there is non-direct influence of retail service quality on customer loyalty through customer satisfaction of 41% at IKEA Alam Sutera. Keywords: customer loyalty, customer satisfaction, retail service quality